PHYTOPHTHORA CACTORUM (LEBERT & COHN) J. SCHRÖT AS CAUSAL AGENT OF DIEBACK OF CHESTNUT AND APPLE TREES IN MACEDONIA - Risteski, Mihajlo; Woodward, Stephen; Ježić, Marin; Rusevski, Rade; Kuzmanovska, Biljana; Sotirovski, Kiril (Macedonian Academy of Sciences and Arts, 2019)
From 2013–2017, 11 chestnut populations and 16 apple orchards/plantations in Macedonia were examined for health; soil, root and bark samples were collected from trees expressing symptoms regarded as Phytophthora specific. Using leaf baits of Prunus laurocerasus and selective V8 Agar (PARPNH), 19 pure Phytophthora sp. cultures were isolated and identified as P. cactorum by ITS sequencing. Sixteen isolates were from apple trees and 3 from chestnut trees. Phylogenetic analyses suggested slight distance between P. cactorum isolates originating from chestnut trees compared to those from apple orchards. Assessment of pathogenicity using chestnuts twigs showed no differences be-tween P. cactorum isolates from the two tree host species.